1988
DOI: 10.1002/1097-0142(19880115)61:2<221::aid-cncr2820610203>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly from ectopic growth hormone-releasing hormone secretion by a malignant carcinoid tumor.Successful treatment with long-acting somatostatin analogue SMS 201–995

Abstract: A 26-year-old man with acromegaly secondary to ectopic growth hormone-releasing hormone (GHRH) secretion by a metastatic carcinoid tumor is the subject of this study. He previously failed to respond to conventional therapeutic modalities (partial hypophysectomy, pituitary irradiation, highdose bromo-criptine and a combination of streptomtwin and 5-fluorouracil) and was treated with long-acting so-matostatin analogue SMS 201-995 (Sandoz, East Hanover, NJ). Growth hormone and somatomedin C concentrations became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Somatostatin analogs provide an effective option for medical management of carcinoid patients, especially those with recurrent disease. In fact, somatostatin analog therapy may slow tumor progression in some patients with neuroendocrine tumors [90,92]. Administration of the analog is able to lower circulating GH and IGF-1 levels by suppressing ectopic tumor production of GHRH [93].…”
Section: Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Somatostatin analogs provide an effective option for medical management of carcinoid patients, especially those with recurrent disease. In fact, somatostatin analog therapy may slow tumor progression in some patients with neuroendocrine tumors [90,92]. Administration of the analog is able to lower circulating GH and IGF-1 levels by suppressing ectopic tumor production of GHRH [93].…”
Section: Treatmentmentioning
confidence: 97%
“…In most of the published studies, medical therapy of acromegaly due to ectopic GHRHsecreting tumors with octreotide or lanreotide over a period of 2.5-36 months did not achieve a significant shrinkage of primary or metastatic neoplastic lesions. On the other hand, Barkan et al [90] observed a significant shrinkage of lung, bone, and liver metastases of a carcinoid of unknown origin under long-term treatment with octreotide at very low doses (100 µg/d) without obtaining, however, any normalization in GHRH plasma levels.…”
Section: Treatmentmentioning
confidence: 99%
“…The second possibility is that the thyroid goiter might have produced ectopic GHRH. This hormone is reported to be secreted by pancreatic, pulmonary and intestinal endocrine tumors and by sympathetic neuronal tumors (5,6). Some medullary carcinomas of the thyroid may contain immunoreactive GHRHtissue (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1: 984 ng/ml (63-380), GH: 49.8 ng/ ml (<5), PRL: 23.3 ng/ml (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), testosterone: 3.6 ng/ml (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), LH: 2.0 mIU/ml (2)(3)(4)(5)(6)(7)(8), FSH: 3.9 mIU/ml (2)(3)(4)(5)(6)(7)(8), mid-molecule PTH: 31.2 pg/ml (£125), gastrin: 29 pg/ml (£90), 5-hydroxyindoleacetic acid: 9 mg/24 h (£6), serum chromogranin A: 20 nmol/l (<4).…”
Section: Biochemical Examinationsmentioning
confidence: 99%
“…Although experience is still limited (only 19 patients to our knowledge) [5,7,8], somatostatin (SMS) analogs have been used in the treatment of ectopic acromegaly since they may not only control the endocrine hypersecretion but also tumor proliferation. Despite the favorable clinical improvement documented for most of the patients, the significant decrease in GH and insulin-like growth factor 1 (IGF-1) [9][10][11][12] and shrinkage of the previously hyperplastic pituitary gland [7,12], the response of the GHRH-producing tumor and its metastases is less predictable and tumor size can increase despite suppression of the GH axis [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%